Effects of different routes of nicotine administration on gastric morphology and hormonal secretion in rats. Issue 8 (5th July 2015) - Ali, Soad Shaker; Hamed, Enas Ahmed; Ayuob, Nasra Naeim; Shaker Ali, Ahmed; Suliman, Mansour Ibrahem
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Does chronic administration of nicotine by different routes affect gastric hormonal secretions and morphology in rats? What is the main finding and its importance? Chronic nicotine administration increased levels of gastrin, ghrelin and histamine but decreased prostaglandin E2. Nicotine administered orally and by inhalation had a marked negative impact on the histological structure of the gastric mucosa compared with intraperitoneal administration. The negative impact of nicotine administration on gastric structure was associated with an increased concentration of gastrin and decreased prostaglandin E2, which might be the cause of gastric/peptic ulcers in heavy smokers. The increase in ghrelin concentration and its effect following chronic nicotine administration needs further investigation. The aim was to assess the effects of different routes of chronic nicotine administration on gastric morphology and hormonal secretion; mainly gastrin, ghrelin, histamine and prostaglandin E2 (PGE2). Forty adult male albino rats were randomly assigned into four groups (10 rats per group), treated for 21 days as follows: control group (given standard rat pellets and water only); oral nicotine‐treated group [50 μg (ml drinking water)−1]; intraperitoneal nicotine‐treated group [0.5 mg (kg body weight)−1]; and inhaled nicotine‐treated group [0.5 mg (kg body weight)−1]. Concentrations of gastrin, ghrelin, PGE2 and histamine in serum and gastric tissue homogenates were assessed using ELISA kits. Stomach fundus was processed for histopathology and immunohistochemistry using light and electron microscopy. Different routes of chronic nicotine administration resulted in a significant increase in serum and gastric homogenate gastrin and ghrelin concentrations and a significant decrease in serum and homogenate PGE2 concentrations compared with the control group. Moreover, nicotine administration via oral and inhalation routes caused gastric erosion, transformation of peptic cells into the mucous variety, a significant increase in parietal cell numbers and an increase in expression of gastrin. In conclusion, the negative impact of nicotine administration on gastric structure that is associated with an increased concentration of gastrin and decreased concentration PGE2 might be the leading cause of gastric/peptic ulcers in heavy smokers. The increased ghrelin concentration and its effect following nicotine chronic administration needs further investigation. Based on these findings, we suggest that the alteration in gastric structure following chronic administration of nicotine can be prevented by reducing gastrin secretion and/or targeting its receptors.